A Scratch Programming Workshop for High School Girls: Engagement, Learning, and Inclusion in Computing - Coutinho, Fernanda; Souza, Isadora de; Dias, Lara; Lindebeck, Juliana; Valle, Pedro Henrique Dias; Oliveira, Alessandreia Marta de (Anais do Women in Information Technology (WIT); 2026: Anais do XX Women in Information Technology, 2026)
Computational Thinking (CT) has been recognized as a key component in students’ development, strengthening abilities such as creativity, autonomy, and problem-solving. This work presents a workshop for high school girls from a public school using Scratch to introduce programming concepts and encourage girls’ participation in Computing. The initiative provides an accessible and interactive learning experience that supports digital skills and promotes a more inclusive approach to programming education. Results show that most students achieved “Adequate” and “Excellent” levels in skills involving abstraction, algorithms, and data analysis, suggesting assimilation of CT concepts and the potential of the workshop to foster girls’ engagement in Computing.